Exploratory Excitability and Sensation Seeking as Moderating Factors on the Mere Exposure Effect - Tiliopoulos, Niko; Au, Jacky; Lesmana, Cokorda Bagus Jaya (ANIMA Indonesian Psychological Journal, 2013)
The mere exposure effect (Zajonc, 1968) proposes that repeated exposure to a stimulus enhances one’s attitude towards it. The present study examined the moderating effects of sensation seeking and exploratory excitability on the mere exposure effect. Eighty-five females were exposed to photographs of faces subliminally. Participants completed the Sensation Seeking Scale (SSS-V) and the IPIP Variety-seeking questionnaires and provided liking and recognition ratings for faces previously viewed 0, 1, 2, 5, 10, or 25 times. Liking ratings did not vary as a function of exposure frequency. Sensation seeking failed to moderate the effect of exposure on liking for facial stimuli. Exploratory excitability appeared to interact with frequency of exposure, such that higher variety- seeking was associated with an increased liking for novel faces and a decreased liking for repeatedly exposed faces but the significance of this finding was questionable. Interpretation of these results, methodological limitations and directions for future research are discussed. Efek paparan sederhana (Zajonc, 1968) mengusulkan bahwa paparan berulang pada suatu stimulus meningkatkan sikap seseorang ke arah paparan. Penelitian ini meneliti efek kendali dari pencarian sensasi dan rangsangan eksplorasi pada efek paparan sederhana. Delapan puluh lima perempuan ditunjukkan foto-foto wajah secara terselubung. Peserta menyelesaikan Sensation Seeking Scale (SSS-V) dan kuesioner IPIP variety-seeking dan memberikan tingkat pengakuan dan keinginan untuk foto-foto wajah yang dilihat sebelumnya sebanyak 0, 1, 2, 5, 10, atau 25 kali. Tingkat menyukai tidak bervariasi dalam fungsi dari tingkat paparan. Mencari sensasi gagal mengendalikan pengaruh paparan terhadap keinginan untuk rangsangan wajah. Rangsangan eksplorasi terlihat berinteraksi dengan frekuensi paparan, seperti dalam hal ragam keinginan yang lebih tinggi dikaitkan dengan meningkatnya keinginan menyukai wajah yang baru dan menurun menyukai paparan wajah yang berulang, tetapi kemaknaan dari temuan masih dipertanyakan. Interpretasi dari hasil, keterbatasan metodologi dan arah untuk penelitian lanjutan dibahas dalam studi ini.